Cyclic shift resolution effects on OFDM system employing cyclic-SLM with delayed correlation and matched filter - Pamungkasari, P.; Sanada, Y.; Juwono, Filbert Hilman; Gunawan, D. (2017)
© 2017 IEEE. Large peak-to-average power ratio (PAPR) is the major issue in orthogonal frequency-division multiplexing (OFDM) systems. Selective mapping (SLM) has been commonly employed to reduce the PAPR. However, SLM requires side information (SI) which reduce the bandwidth efficiency. A low-complexity cyclic SLM (C-SLM) scheme without SI which uses delay correlation and matched filter, called C-SLM-DC-MF, has been proposed in the literature. This paper examines the effects of cyclic shift resolution of the OFDM system with C-SLM-DC-MF scheme on the system performance, in terms of PAPR reduction, accuracy, and bit error rate (BER). Simulation results show that higher resolution leads to lower PAPR reduction but better accuracy and BER performance.